Anthropometric characteristics and physical fitness in elite futsal male players. A systematic review - Stubbs-Gutierrez, A.; Medina-Porqueres, I. (Movement & Sport Sciences - Science & Motricité, 2020)
The purpose of the study was to summarize scientific literature on anthropometric characteristics and physical condition in high-level futsal male players. Potentially relevant publications were identified by searching electronic databases from inception to September 2019. Selected studies were independently reviewed for methodological quality and assigned a level of evidence. A total of 10 articles comprised this review, all of them being observational designs. Physical fitness studies included power, speed, agility, flexibility, and functional tests, maximum oxygen consumption (VO2max) and ventilatory threshold (VT) testing. PEDro scale values ranged from 4 to 7, with an average of 5.7 and low/moderate to moderate/strong methodological quality. Futsal players tend to show different physical profiles depending on their position. In general, field futsal players present higher VO2max, VT, and heart rate values than goalkeepers. Together with these findings, more interventional studies are needed for the purpose of defining proper physiological and anthropometric profile in high-level futsal.